Escala lúdica pré-escolar de Knox - delineamento metodológico das pesquisas - Scofield, Izadora Ramos (Universidade Federal de São Carlos, 2022)
Introduction: Playing is intrinsically related to child development. Through play assessment, health professionals, including occupational therapists, can obtain information about child development. The Knox Preschool Play Scale - revised (ELPK-r) is a standardized, effective assessment, capable of assessing the skills that exist during preschooler’s play behavior. The ELPK-r describe the typical evolution of play in four domains: space management, material management, make-believe/symbolic, and participation in 6-month periods from 0 to 3 years of age and in annual periods from 3 to 6 years of age. Aim: To examine the national and international scientific production about the ELPK-r. Method: This is a scoping review of the literature, utilizing the following research databases: Capes, Scopus, Lilacs, BDENF, Embase, Cochrane, Medline, PubMed, CINAHL, Web of Science, PsycINFO, Scielo, Google Scholar, Dedalus, BDTD e PROQUEST. The search strategy included the descriptors: “Escala Lúdica Pré-escolar de Knox” OR “Knox Preschool Play Scale”. Rayyan literature review software was used. The steps for conducting the research were: (1) define the research question; (2) select the databases; (3) define the descriptors; (4) identify the relevant studies; (5) select the studies; (6) map the data; (7) examine, discuss and report the data obtained. Results: 424 studies were identified. Out of these, 208 duplicates were excluded, 156 after reading the title and abstract, and 27 after reading in their entirety because they did not meet the inclusion criteria, leaving 33 studies. After this step, 13 articles from the authors' repository were manually included, totaling 46 studies published between 1989 and 2019. 18 observational cross-sectional analytical studies, 8 experimental analytical studies, 2 observational cohort analytical studies, 6 methodological studies of instrument validation and/or cultural adaptation, and 12 descriptive studies were identified. Conclusions: This review showed that ELPKr has reliable evidence and a useful scientific basis for professionals working with preschoolers. Many of the studies reviewed aimed to analyze, describe, and compare different patterns of play behavior in preschool children, proving the usefulness of ELPK-r in clinical practice.
Knox preschool play scale - research methodological design
Keywords: Criança; Desenvolvimento infantil; Jogos e brinquedos; Terapia ocupacional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL